Uso excesivo de papel en los procesos aduaneros: Caso de la Dirección de Impuestos y Aduanas Nacionales – seccional Aduanas Cartagena (2014)
The goal of this article is to analyze the DIAN’s efficiency and efficacy on custom operation processes, based on paper use which take place in those processes, to identify bad practices on document management and finally, to propose solutions to improve the performance of custom operations. The methodology of this article is exploratory and descriptive. As the main conclusion, this article states that the DIAN’s missionary activities should be according to the clean operation processes, DIAN’s employees should rationalize their use of resources as paper and give a breath to the planet through the environmental culture at office, however, it is important that the State join together with so the good actions be from all to all.